Dilemma in diagnosing ovarian ectopic pregnancy - Rajpal, Harsha; Kaur, Harvinder; Miglani, Urvashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
To study different presentation of ovarian ectopic pregnancy and its management. All the 4 patients of ovarian ectopic pregnancy presented in our hospital in the month of April 2019 were analysed. We reported 4 cases with a pre-operative provisional diagnosis of ruptured ectopic pregnancy and intra-operative diagnosis of? ovarian ectopic pregnancy, however histopathological examination confirmed the diagnosis of ovarian ectopic pregnancy in only 2 of the cases while the other 2 were ruptured corpus luteal cyst. Wedge resection was performed in all 4 patients. Ovarian ectopic pregnancy is rare and can be missed radiologically and intra-operatively. Establishing early diagnosis is a challenge to the clinician, it commonly mimics tubal ectopic or ruptured corpus luteal cyst. Provisional diagnosis can be made intra-operatively when a hemorrhage mass is seen near the ovary with a normal fallopian tube but can be confirmed by histopathological examination. The chief goal of the treatment remains life-saving intervention by early diagnosis to reduce maternal mortality and morbidity.